Treatment policy of surgery in small cell carcinoma of the lung: retrospective analysis of a series of 874 consecutive patients. Issue 4 (April 1985) - Osterlind, K; Hansen, M; Hansen, H H; Dombernowsky, P; Rørth, M
Abstract : A therapeutic policy of surgery in the treatment of small cell carcinoma of the lung was evaluated in a retrospective series of 874 consecutive patients. All patients were included in one of six clinical trials of intensive combination chemotherapy and radiotherapy, carried out during 1973-81. General criteria of resectability, including normal appearances at mediastinoscopy, were fulfilled in 33 electively operated patients and in 46 non-operated patients. An elective operation was defined as a thoracotomy performed with the intention of pulmonary resection in a patient known to have small cell carcinoma. Pneumonectomy or lobectomy was performed in 73% of the electively operated patients. Residual macroscopic or microscopic tumour tissue was left after half of these resections. Both operated patients and non-operated patients with operable tumours survived significantly longer than 696 patients deemed to have been inoperable. There was no significant difference, however, in the duration of survival between the two subsets of operable patients. According to this analysis, a treatment policy of surgery for resectable small cell carcinoma does not lead to better overall results than treatment with chemotherapy and radiotherapy alone.